2014
DOI: 10.1155/2014/248103
|View full text |Cite
|
Sign up to set email alerts
|

Persea declinata (Bl.) Kosterm Bark Crude Extract Induces Apoptosis in MCF‐7 Cells via G0/G1 Cell Cycle Arrest, Bcl‐2/Bax/Bcl‐xl Signaling Pathways, and ROS Generation

Abstract: Persea declinata (Bl.) Kosterm is a member of the Lauraceae family, widely distributed in Southeast Asia. It is from the same genus with avocado (Persea americana Mill), which is widely consumed as food and for medicinal purposes. In the present study, we examined the anticancer properties of Persea declinata (Bl.) Kosterm bark methanolic crude extract (PDM). PDM exhibited a potent antiproliferative effect in MCF-7 human breast cancer cells, with an IC50 value of 16.68 µg/mL after 48 h of treatment. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Rice bran phytic acid was reported to induce apoptosis via regulation of Bcl-2/Bax in HepG2 cells (22) and Persea declinata (Bl.) Kosterm bark methanolic crude extract induced cell apoptosis through upregulation of Bax and downregulation of Bcl-1 in human breast cancer cells (23). In the present study, it was further demonstrated that treatment with DCIVa activated the mitochondrial apoptotic pathway.…”
Section: Discussionsupporting
confidence: 68%
“…Rice bran phytic acid was reported to induce apoptosis via regulation of Bcl-2/Bax in HepG2 cells (22) and Persea declinata (Bl.) Kosterm bark methanolic crude extract induced cell apoptosis through upregulation of Bax and downregulation of Bcl-1 in human breast cancer cells (23). In the present study, it was further demonstrated that treatment with DCIVa activated the mitochondrial apoptotic pathway.…”
Section: Discussionsupporting
confidence: 68%
“…This phenomenon was demonstrated on human endothelial cells and further investigations in plants are necessary. ROS are known to be able to induce cell cycle arrest, which leads to the inhibition of growth (Guo et al, 2014Narrima et al, 2014. However, this effect has been shown on animal (tumor) cell line models and cannot be automatically applied on plant cells despite the fact that we observed inhibition of growth in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 78%
“…Many of the current studies have demonstrated the ability of natural extracts to inhibit the growth and proliferation of cancer cells. 1 34 …”
mentioning
confidence: 99%